Emergence of a Euglena bioconvection spot controlled by non-uniform light - Yamashita, Hiroshi; Kamikubo, Touya; Muku, Kazuki; Suematsu, Nobuhiko J.; Izumi, Shunsuke; Iima, Makoto (Frontiers in Ecology and Evolution, 2023)
Microorganisms possess taxes, which are the behavioral response to stimuli. The interaction between taxis and fluid dynamic instability leads to a macroscopic flow called bioconvection. In this study, we demonstrated that an isolated, single, three-dimensional bioconvection cell can exist within Euglena suspension. The isolated convection cell was named a “bioconvection spot.” To reveal the formation of this bioconvection spot in a cylindrical container, position-control experiments were designed in a non-uniform light environment. Upon exposure of Euglena suspensions to varying light conditions with white and red regions, Euglena was determined to aggregate into the red (darker) region. This was attributed to its phototactic response of Euglena, causing its movement toward a darker environment and away from a strong light. Thus, the bioconvection spot was created by manipulating the local cell density of the suspension and the light environments. Using our experimental setup, we observed the structure of the spot and established that it radiated pulses of local cell densities of Euglena.